Applying Design Science Research Methodology for Development of a Mobile-Based Digital Quail Farming Guide - Ahmad Sofian, Shminan; Siti Nor Ain, Romly; Merikan, Aren; Lee, Jun Choi; Wan Norizan, Wan Hashim (IEEE, 2022)
This study aimed to design and develop a mobile based digital quail farming guide for the B40 elderly group. This mobile application, known as Quaillogy, provides learning materials for basic quail farming and different topics in entrepreneurship and marketing. The underlying motivator is to provide a tool for the B40 household income elderly to learn independently at their own pace about quail farming through mobile devices. The recently increased request for quail production will benefit the target users in becoming beginner breeders and entrepreneurs. Design Science Research Methodology (DSRM) was selected as the methodology that fit the requirement of developing the mobile application. It consisted of six stages: problem identification, definition objective, design and development, demonstration, evaluation, and communication. The evaluations from experts and users’ views were conducted to examine the content and user interface design. In sum, this research achieved the objectives as the evaluations showed positive feedback. Quaillogy does contribute to the elderly by offering knowledge about basic quail farming and exposing them to basic digital marketing strategy knowledge. It indirectly benefits the elderly to initiate quail farming and eventually generate side income to support the upsurge in living expenses. The findings were aligned with several Sustainable Development Goals (SDGs) of “Quality Education”, “No Poverty”, and “Decent Work and Economic Growth”. Knowledge transmission using mobile technology can provide an inclusive and equitable quality of education. At the same time, reducing income inequality and enriching economic growth can eradicate poverty. Future research may also be able to take more advantage of Quaillogy.